"The October Revolution and the Constants of Russian Being". Issue 1 (2nd January 2018) - Nikolsky, Sergey A.
Abstract : In the history of Russia's development, there are clear, unchanging constants of empire, autocracy, and property as power (property/propertilessness). These are persistent structures that have existed over a long historical period, which are created by the state and society, and are upheld by tradition. On the one hand, they are restrictive, but on the other hand, they guide the direction of socioeconomic, sociopolitical, and cultural development, and also facilitate the emergence of the corresponding social actors (individuals or groups) and institutions. During the Russian revolutionary process, which spanned 1905–1922 and reached its apex in the October Revolution, an attempt was made to change these constants. However, this attempt failed, and Russia returned to its traditional path of development.